Profil Kinerja Guru Bimbingan dan Konseling Menurut Persepsi Guru Mata Pelajaran - Monika Lam; Dhiu Margaretha; Gracianus Edwin Tue P. Lejap (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
In the school environment, a good assessment of the performance of guidance and counseling teachers by subject teachers reflects recognition of the contribution of guidance and counseling teachers in supporting students academically, emotionally, and socially. The purpose of this study was to see the views of subject teachers on the performance of guidance and counseling teachers in various aspects. This type of research is quantitative descriptive. The instrument in this study used a questionnaire on the performance of guidance and counseling teachers. Based on the results of the analysis of the research data that have been presented, the researcher concluded that the performance of guidance and counseling teachers was assessed as good according to the perceptions of subject teachers based on several aspects, namely basic services, individual interest and planning services, responsive services and system support services.